Improving Cardiac Rehabilitation Referral Rates in Patients with Coronary Heart Disease from Diverse Communities Using an Electronic Order System - Maloof, Alexandra; Barba, David Torres; Nuño, Santiago Ramirez; Bains, Nainjot K; Zepeda, Ignacio A; Gallegos, Armando; You, Hyeri; Thompson, Wesley; Shen, Jia; El-Kareh, Robert; et al. (Journal of Cardiology and Cardiovascular Medicine, 2024)
Introduction: Despite the benefits of Cardiac Rehabilitation (CR), local and national CR referral and participation rates remain low when compared to established cardiovascular therapies, especially amongst racial/ethnic groups. Objectives: This study investigated the effects of the implementation of a CR program and electronic order set (EOS) in a large health system on CR referral and participation rates among a diverse group of patients with Coronary Heart Disease (CHD). Methods: A total of 360 patients from UCSD Health who presented with ACS were prospectively evaluated during initial hospitalization and 6- and 12-weeks post-discharge. The multivariable logistic regression model assessed referral and participation rates by week 1 and -12 post-discharge, adjusting for gender, age, race, ethnicity, geography, and referring physician subspecialty. Results: UCSD CR program implementation led referral rates to increase at week 1 (Pre- 38.6% and Post-54.9%, p = 0.003) and week-12 (Pre- 54.1% and Post- 59.8%, p = 0.386). Post-CR referrals were more likely at week-1 (OR: 1.93, 95% CI 1.27-2.95) and week-12 (OR: 1.26, 95% CI 0.79-2.00). EOS implementation increased referral rates at week-1 (Pre- 40.3% and Post- 58.7%, p < 0.001) and week-12 (Pre- 54.9% and Post- 60.4%, p = 0.394) with referrals more likely at week-1 (OR: 2.1, 95% CI 1.35-3.29) and week-12 (OR: 1.25, 95% CI 0.795-1.98). Participation in CR following EOS was more likely at both week-1 and week-12. Multivariable analysis revealed disparities in referral based on race, geographic location, and referring physician subspecialty. Conclusion: A CR program and EOS implementation were shown to increase referral rates with long-term potential for increasing referral and participation rates. Condensed abstract: This prospective study investigated the implementation of a Cardiac Rehabilitation (CR) program and Electronic Order Set (EOS) within the same health system on CR referral and participation rates. 360 patients with ACS were evaluated over 12 weeks. UCSD CR program and EOS implementation led referral rates to increase at week-1 and -12. CR participation was more likely to increase at week-1 and -12 following EOS. Multivariable analysis revealed disparities in referrals disproportionally affecting racial and ethnic minority groups and rural communities. CR and EOS implementation may increase CR referral rates for diverse patients with CHD.